Unraveling the association of bacteria and urinary stones in patients with urolithiasis: an update review article - Razi, Abdolah; Ghiaei, Azita; Dolatabadi, Fahimeh Kamali; Haghighi, Ramin (Frontiers in Medicine, 2024)
Urinary stone disease (USD) is a prevalent urological condition, ranking as one of the most common urinary tract disorders globally. Various risk factors influence the formation of kidney stones, and recent research indicates a rising prevalence of urolithiasis worldwide, particularly in developing countries. While the morbidity associated with urinary stones has decreased in recent years, long-term complications such as stone recurrence, kidney failure, and uremia continue to burden patients. Understanding the etiologies of urolithiasis, including the role of bacteria, is crucial as they can contribute to stone recurrence. The incidence of urinary tract infection (UTI) stones can be attributed to specific infectious risk factors, socio-demographic factors, and comorbid metabolic disorders. This review article explores the emerging evidence suggesting the involvement of bacteria in USD. It discusses the potential role of microorganisms in non-infection stones and highlights the association between UTIs and urolithiasis. Furthermore, it surveys the relationship between kidney stones and recurrent UTIs and the formation of bacterial biofilms in UTIs. Considering various risk factors, including biochemical stone analysis and the presence of bacteria, is essential for treating patients with infectious stones optimally. This review aims to provide an updated understanding of the association between bacteria and urinary stones in patients with urolithiasis, shedding light on the pathophysiology of urinary stone formation, urinary stone characteristics, and the urinary microbiome in urinary stones.